Barrier mechanisms in neonatal stroke - Kratzer, Ingrid; Chip, Sophorn; Vexler, Zinaida S. (Frontiers in Neuroscience, 2014)
Clinical data continue to reveal that the incidence of perinatal stroke is high, similar to that in the elderly. Perinatal stroke leads to significant morbidity and severe long-term neurological and cognitive deficits, including cerebral palsy. Experimental models of cerebral ischemia in neonatal rodents have shown that the pathophysiology of perinatal brain damage is multifactorial. Cerebral vasculature undergoes substantial structural and functional changes during early postnatal brain development. Thus, the state of the vasculature could affect susceptibility of the neonatal brain to cerebral ischemia. In this review, we discuss some of the most recent findings regarding the neurovascular responses of the immature brain to focal arterial stroke in relation to neuroinflammation. We also discuss a possible role of the neonatal blood-CSF barrier in modulating inflammation and the long-term effects of early neurovascular integrity after neonatal stroke on angiogenesis and neurogenesis.